2018
DOI: 10.1017/qua.2018.52
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, nature, and formation of palaeosurfaces within dunes on Fuerteventura

Abstract: The appearances of palaeosurfaces intercalated into palaeo-dune fields on Fuerteventura are multifaceted. Although reddened layers in these dune sediments might suggest that strong soil-formation processes have taken place, the combination of aridity and parent material, namely biogenic carbonate sand of shelf origin, reveals that strong soil formation seems unlikely. These sediments rather represent de- and recalcification processes only. Solely in the case of admixed material of volcanic origin and dust depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…Nevertheless, given its proximity to the Canary Islands, Africa is the simplest choice for the source of such sediments. This interpretation is supported by the abundant evidence for African dust inputs to Canarian soils and paleosols during the Holocene and Pleistocene (Muhs et al, 2010;Huerta et al, 2015;Menéndez et al, 2019;Roettig et al, 2019).…”
Section: Paleoclimatic Implications Of African Dust Inputs To Paleosomentioning
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, given its proximity to the Canary Islands, Africa is the simplest choice for the source of such sediments. This interpretation is supported by the abundant evidence for African dust inputs to Canarian soils and paleosols during the Holocene and Pleistocene (Muhs et al, 2010;Huerta et al, 2015;Menéndez et al, 2019;Roettig et al, 2019).…”
Section: Paleoclimatic Implications Of African Dust Inputs To Paleosomentioning
confidence: 82%
“…1a). African dust is reported as a component of modern soils on the Canary Islands (Muhs et al, 2010) and is also found in paleosols of Pleistocene age (Huerta et al, 2015;Muhs et al, 2016;Menéndez et al, 2019;Roettig et al, 2019). These studies have demonstrated the presence of an African dust component by identification of minerals exotic to the Canary Islands.…”
Section: Introductionmentioning
confidence: 94%
“…Based on Roettig et al (2017), the Quaternary aeolianites on northern Fuerteventura mainly consist of aeolian sands derived from the shelf, volcanic ash and long‐range transported dust. The formation of palaeosurfaces is related to periods of very weak soil formation (restricted to the processes of de‐ and recalcification as well as oxidation of iron and manganese) and dust imprint accompanied by a reduced supply of carbonate sands originating from the shelf (Roettig et al , 2019). The materials involved clearly influence the magnetic parameters and ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Those materials shape the palaeosurfaces which were established during periods of little or no sand accumulation. Dust accumulation is assumed to be the dominant factor, whereas soil‐forming processes are expected to be of minor intensity (Roettig et al , 2019). These archives of alternating aeolianite–palaeosurface sequences offer the possibility to get a detailed understanding of the palaeoenvironmental conditions of the island.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation